Is Protean Career Attitude Beneficial for Both Employees and Organizations? Investigating the Mediating Effects of Knowing Career Competencies - Sultana, Razia; Malik, Omer Farooq (Frontiers in Psychology, 2019)
The aim of this study was to investigate the direct and indirect effects of protean career attitude on subjective and objective career success representing personal outcomes and task performance reflecting an organizational outcome. Drawing on the intelligent career framework, three knowing career competencies i.e., career insight (knowing why), networking (knowing whom), and career/job-related skills (knowing how) were hypothesized as mediators linking protean career attitude with its personal and organizational outcomes. Participants of the study were 241 senior faculty members and matched supervisors from five large public sector universities in Islamabad, Pakistan. Data were collected in two waves through a personally administered questionnaire and analyzed through covariance-based structural equation modeling (CB-SEM). Results showed that protean career attitude has direct positive impacts on subjective career success, objective career success, and task performance. Further, the mediating role of three knowing career competencies was partially supported. We contribute to the literature by proposing and testing a research model linking protean career attitude with its personal and organizational outcomes directly and indirectly through three ways of knowing. A number of practical implications along with future research directions are also discussed.